Diseño editorial y multimedia sobre la gastronomía ancestral del cantón Santiago de Píllaro. - Bonifaz Díaz, Edgar Fernando (2020)
The objective of the Editorial and Multimedia Design is to be used as a mean of theoretical, visual, scientific, biographical and photographic information, int this case the ancestral gastronomy of the city “Santiago de Píllaro” of Tungurahua province showed the need of design an editorial and multimedia magazine offering the ancestral gastronomy of Santiago de Píllaro city, in order to preserve the ancestral knowledge, customs and utensils used in the ancestral gastronomy. Particularly in the rural areas of the city, because the low attention that these places have received, which offer ancestral cuisine in the city, this has caused problems due to the low affluence of tourists visiting these places, despite of presenting a variety of options at the time of promoting local rural tourism, as a result that in recent years the efforts have been focused on prioritizing only the downtown of the city, forgetting the rural sector. It also proposes the creation of a logo, a gastronomic guide and a website, using the Design thinking design methodology proposed by Francisco Cano that is based on how a design philosophy or a framework, which groups methods of design and design research tools were used. As a final result of the editorial and multimedia research, an editorial gastronomic guide, also a website where several places that offer ancestral gastronomy in Santiago de Píllaro city were developed. Through the investigation carried out, it was possible to verify the hierarchy that ancestral knowledge has in Píllaro City , being this the land of the Rumiñahui Inca, the inhabitants of the city feel the senses of belonging with their panzalean roots, for this reason, it was necessary to carry out an editorial and multimedia project where these cultural identity features are presented through the use of design toll such as: diagramming, photography, web layout and visual and multimedia design in order to disseminate the culinary ancestral knowledge of the city through the elements of graphic design suitable for gastronomic publications.